Apocalyptic and Covenant: Perspectives on Paul or Antinomies at War? - Shaw, David A. (Journal for the study of the New Testament, 2013)
The terms ‘apocalyptic’ and ‘covenantal’ are ubiquitous in Pauline studies and are increasingly set against one another as competing lenses by which to view Pauline theology. In search of clarity behind the terminology, this article traces two shifts in recent apocalyptic readings of Paul. First, there is a rhetorical shift which increasingly sets a cosmological apocalyptic reading of Paul against one focused on forensic and covenantal concerns. Secondly, one can detect a theological shift which actually brings the apocalyptic reading of Paul closer to a view that sees a fulﬁlment of the prophetic promise of the new covenant in his theology and ministry. In closing, the two arguments most often advanced to resist such a marriage of approaches are challenged; namely, the view that Paul belongs to a cosmological and not forensic stream of Jewish apocalyptic thought, and the argument that, whatever Paul is doing in earlier chapters, forensic language is absent from, or peripheral to, Rom. 5–8.